Managing shopping experience through mall attractiveness dimensions: An experience of Indian metro cities. Issue 4 (12th September 2016) - Tandon, Anushree; Gupta, Ashish; Tripathi, Vibhuti
Abstract : Purpose: The purpose of this paper is to understand the dimensions of mall attractiveness for Indian shoppers from the metro cities of New Delhi, Kolkata, Chennai and Mumbai; and subsequently investigate the effect of these dimensions on shoppers' mall experience. Design/methodology/approach: A shopper intercept survey was conducted in the aforementioned cities and 400 responses were obtained which were analysed with exploratory factor analysis and stepwise regression. Findings: The results indicate that tenant management, facilities management, atmospherics and entertainment potential are the factors which attract shoppers to malls. Tenant management, facilities management and atmospherics also emerge as significant predictors of mall shopping experience. Research limitations/implications: Due to limited resources, the research results may lack generalizability. Therefore, researchers are encouraged to test the derived factors and hypothesized relationships further. Practical implications: Contemporary retail settings have transited to offer holistic experiences, generated out of tenant mix, facilities and atmospherics. Managers of shopping malls can enhance their mall attractiveness by identifying an optimal mix of factors such as crowd management, tenant variety, parking, etc. as seen in the results of this study. Entertainment emerges as a mall attractiveness dimension but not as a significant predictor of shopping experience which shows that Indian shoppers' inclination towards hedonism is still in elementary stages and economic pursuit continues to be a dominant motivator for visiting a mall. Originality/value: This paper attempts to provide a holistic overview of mall attractiveness dimensions in India and its implications for shopping experiences.